Localization and characterization of cutaneous neurogenic inflammation in acute gastric mucosal injury in rats: A possible morphological explanation for visceral sensitization? - Shi-yi Qi; Jin-wen Lin; Shi-hao Wang; Li-li Lin; Shen Lin; Jian-guo Chen; You-cong Ni; Xin Du; Ling-Ling He; Xin Wu; Dong Lin (PLoS ONE, 2025)
This investigation transcends traditional methodologies by providing a quantitative analysis of the dynamic relationship between visceral pathologies and neurogenic spots, employing an acute gastric mucosal injury (AGMI) rat model to map the somatotopic distribution of visceral sensitization. Through hydrochloric acid-induced plasma extravasation and Evans Blue dye (EB) marking, coupled with a geospatial grid system and multivariate statistical analysis, we identified Feature Regions (FRs) with distinct neurogenic responses. Notably, the right T10-13 dermatomere, or FR-11’, exhibited elevated levels of nociceptive neuropeptides and serotonin, indicative of its significant role in pain perception. The application of electroacupuncture at FR-11’ revealed enhanced therapeutic outcomes compared to the conventional acupoint BL-21, positioning it as a promising modality for the management of visceral pain. These findings contribute substantially to our understanding of the mechanisms underlying visceral-somatic pain and pave the way for innovative pain management interventions in clinical settings.